Responsibility in International Law: General Principle or Institution of Customary Law? - Czaplińska, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The present contribution addresses some fundamental, but still unresolved, issues concerning the sources of international law – the mutual relations and interactions between them and the determination of the character of particular norms of international law in the context of their assignment to the appropriate sources. However, it is done by a means of reference to a specific case of norms concerning international responsibility. As the examination of their nature will show, a relationship between different sources may not necessarily be hierarchical or exclusive; it may be just complementary and evolving.
Keywords: interational responsibility; customary law; general principle